Differential TM4SF5‐mediated SIRT1 modulation and metabolic signaling in nonalcoholic steatohepatitis progression. Issue 1 (22nd October 2020) - Ryu, Jihye; Kim, Eunmi; Kang, Min‐Kyung; Song, Dae‐Geun; Shin, Eun‐Ae; Lee, Haesong; Jung, Jae Woo; Nam, Seo Hee; Kim, Ji Eon; Kim, Hye‐Jin; Son, Taekwon; Kim, Semi; et al.
Abstract: Nonalcoholic fatty liver disease is a chronic condition involving steatosis, steatohepatitis and fibrosis, and its progression remains unclear. Although the tetraspanin transmembrane 4 L six family member 5 (TM4SF5) is involved in hepatic fibrosis and cancer, its role in nonalcoholic steatohepatitis (NASH) progression is unknown. We investigated the contribution of TM4SF5 to liver pathology using transgenic and KO mice, diet‐ or drug‐treated mice, in vitro primary cells, and in human tissue. TM4SF5‐overexpressing mice exhibited nonalcoholic steatosis and NASH in an age‐dependent manner. Initially, TM4SF5‐positive hepatocytes and liver tissue exhibited lipid accumulation, decreased Sirtuin 1 (SIRT1), increased sterol regulatory‐element binding proteins (SREBPs) and inactive STAT3 via suppressor of cytokine signaling (SOCS)1/3 upregulation. In older mice, TM4SF5 promoted inflammatory factor induction, SIRT1 expression and STAT3 activity, but did not change SOCS or SREBP levels, leading to active STAT3‐mediated ECM production for NASH progression. A TM4SF5‐associated increase in chemokines promoted SIRT1 expression and progression to NASH with fibrosis. Suppression of the chemokine CCL20 reduced immune cell infiltration and ECM production. Liver tissue from high‐fat diet‐ or CCl4 ‐treated mice and human patients exhibited TM4SF5‐dependent steatotic or steatohepatitic livers with links between TM4SF5‐mediated SIRT1 modulation and SREBP or SOCS/STAT3 signaling axes. TM4SF5‐mediated STAT3 activation in fibrotic NASH livers increased collagen I and laminin γ2. Both collagen I α1 and laminin γ2 suppression resulted in reduced SIRT1 and active STAT3, but no change in SREBP1 or SOCS, and abolished CCl4 ‐mediated mouse liver damage. TM4SF5‐mediated signaling pathways that involve SIRT1, SREBPs and SOCS/STAT3 promoted progression to NASH. Therefore, TM4SF5 and its downstream effectors may be promising therapeutic targets to treat nonalcoholic fatty liver disease. © 2020 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.